The political and ideological contraints to economic management in Brazil, 1945-1963 - Sola, L; Sola, Lourdes (1982)
﻿ The objective of this case study on economic management in Brazil is to evaluate the scope and nature of political and ideological factors which affected the process of policy formation from the redemocratization of the country in 1945 until the breakdown of the democratic regime in 1964. Special emphasis is attributed to the reconstruction of the decision-making processes behind the formulation and execution of an agreed economic strategy intended to promote fast economic growth in the 1950's and to the analysis of the political and ideological factors which made acute disequilibria and recession unmanageable within the democratic framework, in the early 1960's. In order to account for the achievements and vicissitudes of economic management in Brazil we focus on the role and function of the state as the key agent in the process of rendering compatible the requirements imposed by economic necessity and the political priorities arising out of the structure and dynamics of the Brazilian political system. Special emphasis is given to the political actors located within the decision making system in particular the técnicos of differing political persuasions, their economic ideologies and their patterns of political action. The reconstruction of the process of policy formation in democratic Brazil is designed to contribute to the current debate on economic and non-economic determinants of the emergence of authoritarian regimes in Latin America. An introduction to our own approach to this question is provided in Chapter I, in connection with discussions current in the relevant literature. In Chapters II and III, we provide an historic reconstruction of the process of policy formation during the late 1940's and 1950's in order to show how technical knowledge and expertize were mobilized as political resources at the service of an economic strategy which shaped the present pattern of capital accumulation in Brazil. Chapter IV examines the political and ideological factors which explain the resumption of inflationary governmental behaviour and over-reliance on foreign debt in the expansionary phase of the economic cycle. In Chapters V, VI and VII we seek to account for the unmanageability of acute disequilibria and recession in the early 1960's through an analysis of the institutional framework and the extremely unstable political background within which any proponents of stabilization-cum-growth policies would have to act.